A 16-week intervention on mood and life quality in elderly: testing two exercise programs - B.R.R. Oliveira (Cuadernos de Psicología del Deporte, 2021)
The purpose was to examine the effects of strength training program (STP) and multi-component training program (MTP) on mood states in physically active elderly. Thirty Brazilian elderly (female=21; male=9) aged between 65 and 75 years (66.9(4.1) with Body Mass Index (BMI) ranging from 25.6 to 31.0 kg/m2 (28.3(1.2), were enrolled for research. The elderly were randomly assigned into two groups: Strength Training Program (STP; age=66.7(4.4 years, BMI=28.2(1.3 kg/m2) and Multi-Component Program (MTP; age=67.1(3.9 years, BMI=28.5(1.0 kg/m2). STP grouerformed three 1-hour sessions per week, working at a range of 3 sets, 8-10 repetitions, and 2-minute recovery between sets and exercises. MTP grouerformed two different types of exercise sessions: a) 50 minutes of Zumba©, followed by 5-10 minutes of dynamic stretching exercises; b) 40 minutes of body-weight dynamic and static exercises, as well as agility and balance movements. The Profile of Mood States (POMS) was applied to assess mood at baseline and post-intervention. No significant interaction or main effect for group and time was showed for six factors of the POMS. However, the magnitude-based inference showed that MTP is likely beneficial to reduce fatigue. On the other hand, MTP is possibly harmful to increase confusion and to reduce vigor when compared to STP. In practical terms, we can conclude that older people physically active seems to attain an adaptation in mood responses minimizing the additional effects of STP and MTP.